Curriculum and curriculum development in Jamaica with special reference to the primary school - Hawes, Hugh W. R. (Department of Education in Developing Countries, Institute of Education, University of London)
This is an initial report on curriculum development of primary school curriculum in Jamaica. A short survey of social and economic development reveals problems of social disadvantagement and income distribution. Following this, an overall look at educational provision is provided. The government provides financial support for the building, management, and maintenance of the majority of schools but does not prescribe the syllabuses. Consequently, principals have an important influence on curriculum. Problems involve teacher education, teacher wastage, attendance, rural urban differences, overcrowded classes, and financial constraints. New approaches centre on the Curriculum Development Thrust started in 1970 to relate content to the aims of education combined with evaluation criteria, revision of primary school mathematics, and language instruction. These changes are complemented by the inservice teacher education Thrust, which involves a four-year, part-time course. Additionally, preprimary education is being developed and a programme instituted to aid rural schools. Ideas generalizable elsewhere are: the approach to preprimary education, decentralization, the integration of teacher education and curriculum development, and the use of National Service Workers as teachers' aides. Policy, priorities, cost effectiveness, and overcrowded classes need further consideration
Keywords: Curriculum development